Implementasi Sensor Pyroelectric Infra Red (PIR) Sebagai Pewaktu Televisi - As Sadad, Rif’an Tsaqif; Iswanto, Iswanto (Universitas Muhammadiyah Yogyakarta, 2010)
Energy dissipation is very disturbing for a country's survival, including Indonesia. Power dissipation generally occurs because of the lifestyle of people who tend consumptive Indonesia. One example of energy waste in the household is often forgot to turn off the television. The timer on the television was made in order to be able to set how long the TV will die (off) by itself in accordance with a prearranged time. However, not everyone can or know of this timer function, especially those who have elderly. Many cases of elderly people see television to fall asleep without turning it off. In this case certainly happens waste of electricity. In this study will be designing and manufacturing tools that can be used as a detector of movement of people in front of the television, so television is only lights up if there is a movement of people who watch television. From the results of this research tool is able to detect the movement of people in front of the television, with the effective distance of the tool is 2 meters.